Nursing theory : utilization & application (Elsever, 2013)
Nursing Theory: Utilization & Application illustrates the role of theory for patient-focused nursing. It serves as a companion text for Nursing Theorists and Their Work, eighth edition, by Martha Raile Alligood, which provides a more comprehensive overview of the history and development of nursing’s theoretical works.